Alcoholism and going through the existential dilemma - Markevičius, Giedrius (Psichologija, 2000)
This work is based on the paradigm of existential psychology. It is stated that dependence on alcohol is person’s endeavour to decrease the existential suffering. This is analysed by taking into consideration the main life choices. The work abcorbs in a world of alcoholics’ experience and it aims at revelation of their existential dilemmas, gravities and contradictions in a face of human experiences like the end of life, the question of meaning of life, the existential loneliness, the freedom of making the choice, the existential guilt and anxiety. The analysis shows that the experiences described are very paradoxical. The wholiness of being is experienced only through taking into consideration the end of existence. It is possible to give a meaning to the life only by transcending one’s self. The relation between "I-You" is experienced just after grasping one’s separatedness and the freedom is experienced just after accepting the limits. The person becomes responsible when he (she) realizes his (her) existential guilt and anxiety. It is obvious that alcoholic who confronts these paradoxies of being lives through sharp dilemmas and can’t escape from solving them. Even alcoholic’s refusal to choose in the nearest future means his negative choice, that strengthens "existential forgetfulness", the feeling of meaninglessness, loneliness, dependence and neurotic guilt. It deepens significantly the illness and it tempts fo grow intoxicated further. At the opposite, every positive choice of alcoholic encourages him to search for the meaning of life, to experience the wholiness of being, to seek for the close relations, to experience the freedom and responsibillity. It helps to accept one’s illness and to get over, for suve. The investigation of existential dilemmas of alcoholics shows evidently that the use of alcohol is not the most important factor of dependence, but the outcomebehavior of his certain choices and the expression of the unsolved contradictions. It would be valuable to take into consideration this fact in the research of the ethiology of alcoholism and in the health promotion of alcoholics.